INDIVIDUAL CHARACTERISTICS OF YOUNG HANDBALL PLAYERS - Eshmamatova Gulolam Ilhomjon qizi (Web of Journals Publishing, 2026)
The article analyzes the individual characteristics of 13–15-year-old handball players, including anthropometric, physical, functional, and psychological indicators. The importance of an individualized training approach is emphasized.
Keywords: Handball, young athletes, individual characteristics, physical training.